2020
DOI: 10.1021/acs.est.9b05896
|View full text |Cite
|
Sign up to set email alerts
|

In Situ-Formed PdFe Nanoalloy and Carbon Defects in Cathode for Synergic Reduction–Oxidation of Chlorinated Pollutants in Electro-Fenton Process

Abstract: Complete dechlorination and mineralization of chlorophenols via the reduction−oxidation-mediated electro-Fenton process with a composite bulk cathode is first proposed. The in situ formation of a PdFe nanoalloy and carbon defects as key active sites is mutually induced during the formation of a carbon aerogel-based electrode. Specifically, the PdFe nanoalloy promotes the generation of [H] ads as reduction sites and improves the electron transfer via an electrical circuit, while the carbon defects selectively f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(54 citation statements)
references
References 40 publications
(73 reference statements)
0
50
0
Order By: Relevance
“…Electro-Fenton (EF) represents an important eco-friendly version of advanced oxidation processes (AOPs), since the risk in the transportation and operation of H 2 O 2 in the conventional Fenton process could be avoided. In the EF process, a two-electron oxygen reduction reaction (ORR) occurs at the cathode to generate H 2 O 2 , which could subsequently react with ferrous ions (Fe 2+ ) to produce hydroxyl radicals (·OH) . The high redox potential of ·OH (1.8–2.7 V) renders strong oxidation ability to the degradation of various organic recalcitrant pollutants including dyestuffs, pharmaceuticals, and pesticides from food, tanning, and petrochemical industries. However, the EF process suffers from low utilization efficiency of H 2 O 2 for the generation of ·OH as well as undesirable precipitation of iron oxy-hydroxides, because of the rapid accumulation of Fe 3+ via eq but slow regeneration of Fe 2+ via eq . …”
Section: Introductionmentioning
confidence: 99%
“…Electro-Fenton (EF) represents an important eco-friendly version of advanced oxidation processes (AOPs), since the risk in the transportation and operation of H 2 O 2 in the conventional Fenton process could be avoided. In the EF process, a two-electron oxygen reduction reaction (ORR) occurs at the cathode to generate H 2 O 2 , which could subsequently react with ferrous ions (Fe 2+ ) to produce hydroxyl radicals (·OH) . The high redox potential of ·OH (1.8–2.7 V) renders strong oxidation ability to the degradation of various organic recalcitrant pollutants including dyestuffs, pharmaceuticals, and pesticides from food, tanning, and petrochemical industries. However, the EF process suffers from low utilization efficiency of H 2 O 2 for the generation of ·OH as well as undesirable precipitation of iron oxy-hydroxides, because of the rapid accumulation of Fe 3+ via eq but slow regeneration of Fe 2+ via eq . …”
Section: Introductionmentioning
confidence: 99%
“…Although promising PEC performances have been achieved, the charge transfer mechanisms remain unclear and are still under debate in many cases [28,29]. On the other hand, the mass transfer of reactants and their subsequent adsorption on the electrode surface are also essential factors determining the reaction rate and efficiency [30,31]. However, most current prevailing approaches for PEC oxidative upgrading focus on planar photoelectrodes, which suffer from low efficiency caused by limited reactants diffusion around the semiconductor-liquid interface [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pt nanoparticles can activate the surface oxygen species of TiO 2 and become negatively charged, and then, the negatively charged Pt nanoparticles are the active sites for formaldehyde oxidation. Correspondingly, the researchers found that metallic (Pt 0 ) or negatively charged Pt species showed higher oxidation catalytic activity than PtO or Pt 4+ , and H 2 reduction treatment for the supported Pt nanoparticles can improve the catalytic activity at ambient temperature (Figure a–c). On the other hand, several recent studies have investigated the effect of Pt nanoparticles parameters on catalytic performance, such as particle size and dispersion. As the particle size increases, the Pt atoms on the crystal phase increase and provide more active sites for catalytic oxidation .…”
Section: Environmental Catalytic Applicationsmentioning
confidence: 98%
“…This system can degrade RhB within 30 min, and the excess H + generated at the anode can provide a suitable pH environment for the reaction between H 2 O 2 and Fe 2+ to generate HO• (Figure b, c) . In addition, a number of studies found that Pd nanoparticles directly deposited on iron oxides can also simultaneously generate H 2 O 2 and Fe 2+ . , For example, Luo et al developed an electron Fenton system based on Pd/Fe 3 O 4 nanoparticles. The system can remove 98% of phenol (20 mg/L) within 60 min without adding any other chemicals.…”
Section: Environmental Catalytic Applicationsmentioning
confidence: 99%